Targeting Mutated p53 Dependency in Triple-Negative Breast Cancer Cells Through CDK7 Inhibition - Peng, Jingyu; Yang, Ming; Bi, Ran; Wang, Yueyuan; Wang, Chunxi; Wei, Xue; Zhang, Zhihao; Xie, Xiao; Wei, Wei (Frontiers in Oncology, 2021)
Background: Cyclin-dependent kinase 7 (CDK7) is crucial for cell-cycle progression and gene expression transcriptional regulation, which are often unchecked in cancer developing process. CDK7 inhibitors have emerged as promising drugs for treating diverse cancers, including breast cancer. But, the mechanism behind its anticancer effect has not been well investigated. Here, the possible mechanism of CDK7 inhibitors for treating human triple-negative breast cancer (TNBC) has been studied. Methods: The effects of CDK7 inhibitors on breast cancer cells have been identified by measuring cell viability (CCK), cell proliferation, and calculating colony formation. The shRNA and short interfering RNA (siRNAs) were used for the construction of knockdown cells. To assess the expression of associated proteins, western blot was used. Results: This study confirmed that, compared to hormone receptor-positive breast cancer cells, triple-negative breast cancer cells (TNBCs) were more sensitive to THZ1, a novel CDK7 inhibitor. THZ1 treatment specifically downregulated mutated p53 in a dose- and time-dependent manner in TNBC cells. Another CDK7 inhibitor, LDC4297, also potently interfered with the expression of mutated p53. Furthermore, endogenous CDK7 expression was positively correlated with the levels of mutated p53 in TNBC cells. Downregulating mutated p53 expression significantly suppressed the proliferation of TNBC cells. Conclusion: Our findings demonstrated that targeting CDK7 was an effective approach for mutated p53 dependency in TNBC.